Non-stoichiometric hydrogen storage alloy and preparation method thereof
Through the non-stoichiometric composition of La1-a-b-cREaCabMgcNi3.6-dRd and vacuum induction smelting heat treatment technology, the platform pressure and low hydrogen storage of rare earth superlattice hydrogen storage alloys are solved, and high hydrogen storage capacity and The effect of flattening the platform and the preparation method is simple and economical.
Patent Information
- Application Number
- CN202310844533.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing rare earth superlattice hydrogen storage alloys have problems such as low platform pressure or oblique and low hydrogen storage, which is difficult to meet the needs of high hydrogen storage and flat platform pressure.
The non-stoichiometric ratio composition of La1-a-b-cREaCabMgcNi3.6-dRd is used to prepare a non-stoichiometric ratio hydrogen storage alloy through vacuum induction smelting and multi-step heat treatment. The alloy composition is uniform, with high hydrogen storage capacity and high platform pressure, which is easy to activation.
A non-stoichiometric hydrogen storage alloy with high hydrogen storage capacity, flat platform pressure and easy to activate is achieved. The preparation method is simple, the cost is low, and the hysteresis generated by hydrogen absorption and discharge is small.
Smart Images

Figure CN119307785A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage materials and relates to a hydrogen storage alloy, in particular to a non-stoichiometric hydrogen storage alloy and a preparation method thereof. Background Art
[0002] Hydrogen energy is an ideal clean energy with the advantages of large reserves, high calorific value and no pollution. The storage of hydrogen is one of the biggest factors restricting the development of hydrogen energy. At present, the main hydrogen storage methods include high-pressure gaseous hydrogen storage, liquid hydrogen storage, organic liquid hydrogen storage and solid alloy hydrogen storage. Among them, solid alloy hydrogen storage has broad application prospects due to its advantages of high hydrogen storage density, high energy efficiency, good safety and low cost.
[0003] The traditional AB5 type rare earth lanthanide hydrogen storage alloy is one of the most mature and commercial hydrogen storage alloys. It has the advantages of easy activation, high platform pressure and flatness, but its hydrogen storage capacity is about 1.4wt% due to the limitation of crystal structure. In recent years, rare earth superlattice hydrogen storage alloys have gradually attracted extensive attention and research. Its crystal structure contains AB2 and AB5 type subunits stacked in different proportions, showing higher hydrogen storage capacity and easier activation.
[0004] CN111636012B discloses a La-Mg-Ni series hydrogen storage material and a preparation method thereof. The hydrogen storage material is La 1-x-y A x Mg y Ni n B z The alloy, wherein A is Ce, Y, Sm, Pr, Nd or Gd, and B is Mn, Al, Fe, Si, Sn or Cu, is prepared by induction melting and annealing. The hydrogen storage material improves the maximum hydrogen storage capacity and platform pressure of the La-Mg-Ni based hydrogen storage alloy.
[0005] CN112522542B discloses a La-Mg-Ni-Co based two-phase superlattice hydrogen storage alloy and a preparation method thereof. The chemical composition of the hydrogen storage alloy is La 0.75 Mg 0.25 Ni 3.1 Co 0.15 , with A2B7 and A7B 23 The dual-phase structure is sealed in a special nickel shell container and subjected to multi-step heat treatment to obtain a hydrogen storage alloy with excellent electrochemical properties.
[0006] In the prior art, although the performance of rare earth superlattice hydrogen storage alloys is improved compared with the traditional AB5 type rare earth lanthanum series hydrogen storage alloys, they still have disadvantages such as low or inclined platform and low hydrogen storage capacity.
[0007] Therefore, in view of the shortcomings of the existing technology, it is necessary to provide a non-stoichiometric hydrogen storage alloy with large hydrogen storage capacity and flat platform pressure and a preparation method thereof. Summary of the invention
[0008] The object of the present invention is to provide a non-stoichiometric hydrogen storage alloy and a preparation method thereof, so as to improve the hydrogen storage performance of the hydrogen storage alloy and the preparation method is simple and low-cost.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a non-stoichiometric hydrogen storage alloy, wherein the composition formula of the non-stoichiometric hydrogen storage alloy is La 1-a-b-c RE a Ca b Mg c Ni 3.6-d R d , where 0.05≤a≤0.15, 0.2≤b≤0.4, 0.2≤c≤0.4, 0.1≤d≤0.3;
[0011] Wherein, RE includes any one or a combination of at least two of Ce, Y, Sm, Nd or Er;
[0012] R includes any one of Co, Al, Si, Mn, Fe or Zn, or a combination of at least two of them.
[0013] The non-stoichiometric hydrogen storage alloy provided by the present invention has uniform alloy composition, high hydrogen storage capacity and high platform pressure, and is easy to activate.
[0014] Wherein, a is 0.05-0.15, for example, it can be 0.05, 0.08, 0.1, 0.12 or 0.15, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] b is 0.2-0.4, for example, it can be 0.2, 0.25, 0.3, 0.32, 0.35, 0.38 or 0.4, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] c is 0.2-0.4, for example, it can be 0.2, 0.25, 0.3, 0.32, 0.35, 0.38 or 0.4, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0017] d is 0.1-0.3, for example, 0.1, 0.15, 0.2, 0.25 or 0.3, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0018] RE includes any one of Ce, Y, Sm, Nd or Er or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ce and Y, a combination of Nd and Er, a combination of Ce, Y and Sm, or a combination of Sm, Nd and Er.
[0019] R includes any one of Co, Al, Si, Mn, Fe or Zn or a combination of at least two thereof. Typical but non-limiting combinations include a combination of Co and Al, a combination of Si and Mn, a combination of Fe and Zn, a combination of Co, Al and Si, or a combination of Mn, Fe and Zn.
[0020] In a second aspect, the present invention provides a method for preparing the non-stoichiometric hydrogen storage alloy as described in the first aspect, the preparation method comprising the following steps:
[0021] (1) vacuum induction melting the metal raw materials according to the general composition formula of the non-stoichiometric hydrogen storage alloy to obtain a cast alloy;
[0022] (2) The cast alloy obtained in step (1) is sealed, heat treated and stripped in sequence to obtain a non-stoichiometric hydrogen storage alloy.
[0023] Preferably, the power of the vacuum induction melting in step (1) is 5-15kw, for example, 5kw, 8kw, 10kw, 12kw or 15kw, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the vacuum induction melting time in step (1) is 2-4 min, for example, 2 min, 2.5 min, 3 min, 3.5 min or 4 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, after the sealing in step (2), the vacuum degree in the sealed container is -0.06 to -0.09 MPa, for example, it can be -0.06 MPa, -0.065 MPa, -0.07 MPa, -0.075 MPa, -0.08 MPa, -0.085 MPa or -0.09 MPa, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the heating rate of the heat treatment in step (2) is 5-20°C / min, for example, it can be 5°C / min, 10°C / min, 12°C / min, 15°C / min, 18°C / min or 20°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the temperature of the heat treatment in step (2) is 900-1000°C, for example, 900°C, 925°C, 950°C, 975°C or 1000°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the heat treatment time in step (2) is 22-26 hours, for example, 22 hours, 23 hours, 24 hours, 25 hours or 26 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] Preferably, the rotational linear speed of the belt in step (2) is 4-6 m / s, for example, 4 m / s, 4.5 m / s, 5 m / s, 5.5 m / s or 6 m / s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] As a preferred technical solution of the preparation method provided by the present invention, the preparation method comprises the following steps:
[0031] (1) subjecting the metal raw materials to vacuum induction melting for 2-3 minutes according to the general composition formula of the non-stoichiometric hydrogen storage alloy, wherein the temperature of the vacuum induction melting is controlled by the power of the melting furnace, which is 5-15 kW, to obtain a cast alloy;
[0032] (2) The cast alloy obtained in step (1) and 60-100% of the theoretical amount of Mg and 20-30% of the theoretical amount of Ca are coated with tantalum sheets and placed in a container. The container is evacuated and then filled with inert gas to a vacuum degree of -0.06 to -0.09 MPa for sealing. The temperature is then raised to 900-1000°C at a rate of 5-20°C / min for heat treatment for 22-26 hours. After cooling, a belt spinning machine is used for belt spinning treatment. The rotation linear speed during belt spinning is 4-6 m / s to obtain a non-stoichiometric hydrogen storage alloy.
[0033] The theoretical dosage is the dosage of the element calculated according to the composition formula of the non-stoichiometric hydrogen storage alloy.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The non-stoichiometric hydrogen storage alloy provided by the invention has high hydrogen storage capacity, is easy to activate, has high platform pressure, has small hysteresis generated by hydrogen absorption and desorption, and has a simple preparation method and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a curve diagram showing the relationship between the hydrogen absorption amount and time of the non-stoichiometric hydrogen storage alloys prepared in Examples 1-3 of the present invention and Comparative Examples 1-3.
[0037] Figure 2It is a curve diagram showing the relationship between the hydrogen content and the hydrogen pressure of the non-stoichiometric hydrogen storage alloys prepared in Examples 1-3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0039] Example 1
[0040] This embodiment provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La 0.3 Ce 0.05 Y 0.05 Ca 0.3 Mg 0.3 Ni 3.5 Co 0.05 Al 0.05 .
[0041] The preparation method of the non-stoichiometric hydrogen storage alloy comprises the following steps:
[0042] (1) According to the general composition formula, 30 g of metal raw materials were placed in a quartz crucible, with Mg placed at the bottom, Ca, Co, Al, La placed on the top, and Ce and Y sprinkled on the surface. The crucible was first evacuated to 2.0 × 10 -3 Pa and then introduce argon gas to -0.02MPa, and then carry out induction melting, the temperature during melting is 1100°C, the melting time is 2min, the temperature during melting is controlled by the power of the melting furnace, the power for the first 40s is 5kw, the power for the next 40s is 10kw, and the power for the last 20s is 15kw, to obtain a cast alloy;
[0043] (2) The cast alloy obtained in step (1) and 80% of the theoretical amount of Mg and 25% of the theoretical amount of Ca were coated with tantalum sheets and placed in a quartz tube, which was first evacuated to 2.0×10 -3Pa and then introduce argon until the vacuum degree is -0.06MPa to seal the tube. The sealed alloy is annealed, the temperature is raised to 950℃ at a rate of 5℃ / min, kept warm for 26h, and then allowed to cool naturally. The annealed alloy is mechanically polished to remove black oxide scale, and then the alloy is crushed to obtain a bulk alloy. The alloy block is then loaded into a quartz glass tube with an opening at the lower end, and then placed vertically in the induction melting coil of the belt-spinning machine cavity. The cavity is evacuated, and protective gas is filled into the cavity through the belt-spinning machine gas tank. The air pressure of the gas tank is adjusted to be greater than the cavity pressure, so that the induction melted alloy material falls to the surface of the rotating copper roller and is thrown out. The linear speed of the belt-spinning machine is controlled to be 5m / s, and the alloy sheets after belt spinning are mechanically polished to remove black oxide scale, mechanically crushed and sieved through 100 mesh to obtain a non-stoichiometric hydrogen storage alloy.
[0044] The non-stoichiometric hydrogen storage alloy prepared in this embodiment was tested for hydrogen storage performance under a hydrogen pressure of 9 MPa and 100° C. The results are listed in Table 1. The relationship curve between the hydrogen absorption amount and time is shown in Table 1. Figure 1 As shown in the figure, the relationship between hydrogen content and hydrogen pressure is shown in the figure Figure 2 shown.
[0045] Example 2
[0046] This embodiment provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La 0.3 Sm 0.05 Y 0.05 Er 0.05 Ca 0.2 Mg 0.35 Ni 3.5 Co 0.10 .
[0047] The preparation method of the non-stoichiometric hydrogen storage alloy comprises the following steps:
[0048] (1) According to the general composition formula, 30 g of metal raw materials were placed in a quartz crucible, with Mg placed at the bottom, Ca, Co and La placed on the top, and Sm and Y sprinkled on the surface. The crucible was first evacuated to 2.0 × 10 -3 Pa and then introduce argon gas to -0.02MPa, and then carry out induction melting, the temperature during melting is 1100°C, the melting time is 2min, the temperature during melting is controlled by the power of the melting furnace, the power for the first 40s is 5kw, the power for the next 40s is 10kw, and the power for the last 20s is 15kw, to obtain a cast alloy;
[0049] (2) The cast alloy obtained in step (1) and 80% of the theoretical amount of Mg and 25% of the theoretical amount of Ca were coated with tantalum sheets and placed in a quartz tube, which was first evacuated to 2.0×10 -3Pa and then introduce argon until the vacuum degree is -0.07MPa to seal the tube, anneal the sealed alloy, heat it to 950℃ at a rate of 5℃ / min, keep it warm for 24h, and then let it cool naturally, mechanically grind the annealed alloy to remove the black oxide scale, then crush the alloy to obtain a bulk alloy, and then put the alloy block into a quartz glass tube with an opening at the lower end, and then place it vertically in the induction melting coil of the belt-spinning machine cavity, evacuate the cavity, and fill the cavity with protective gas through the belt-spinning machine gas tank, adjust the gas pressure of the gas tank to be greater than the cavity pressure, so that the induction melted alloy material falls to the surface of the rotating copper roller and is thrown out, and the linear speed of the belt-spinning machine is controlled to be 5m / s, and the alloy sheets after belt-spinning are mechanically polished to remove the black oxide scale, mechanically crushed and sieved through 100 mesh to obtain a non-stoichiometric hydrogen storage alloy.
[0050] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this embodiment are listed in Table 1. The relationship curve between the hydrogen absorption amount and time is shown in Table 1. Figure 1 As shown in the figure, the relationship between hydrogen content and hydrogen pressure is shown in the figure Figure 2 shown.
[0051] Example 3
[0052] This embodiment provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La 0.35 Y 0.05 Ca 0.4 Mg 0.2 Ni 3.4 Co 0.10 Mn 0.10 .
[0053] The preparation method of the non-stoichiometric hydrogen storage alloy comprises the following steps:
[0054] (1) According to the general composition formula, 30 g of metal raw materials were placed in a quartz crucible, with Mg placed at the bottom, Ca, Co, Mn, La placed on the top, and Y sprinkled on the surface. The crucible was first evacuated to 2.0 × 10 -3 Pa and then introduce argon gas to -0.02MPa, and then carry out induction melting, the melting time is 4min, the temperature during melting is controlled by the power of the melting furnace, the power of the first 40s is 5kw, the power is 10kw thereafter, and the power of the last 20s is 15kw, to obtain a cast alloy;
[0055] (2) The cast alloy obtained in step (1) and 60% of the theoretical amount of Mg and 20% of the theoretical amount of Ca were coated with tantalum sheets and placed in a quartz tube, which was first evacuated to 2.0×10 -3Pa and then introduce argon until the vacuum degree is -0.09MPa to seal the tube, anneal the sealed alloy, heat it to 900℃ at a rate of 10℃ / min, keep it warm for 26h, and then let it cool naturally, mechanically grind the annealed alloy to remove the black oxide scale, then crush the alloy to obtain a bulk alloy, and then put the alloy block into a quartz glass tube with an opening at the lower end, and then place it vertically in the induction melting coil of the belt-spinning machine cavity, evacuate the cavity, and fill the cavity with protective gas through the belt-spinning machine gas tank, adjust the gas pressure of the gas tank to be greater than the cavity pressure, so that the induction melted alloy material falls to the surface of the rotating copper roller and is thrown out, and the linear speed of the belt-spinning machine is controlled to be 4m / s, and the alloy sheets after belt-spinning are mechanically polished to remove the black oxide scale, mechanically crushed and sieved through 100 mesh to obtain a non-stoichiometric hydrogen storage alloy.
[0056] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this embodiment are listed in Table 1. The relationship curve between the hydrogen absorption amount and time is shown in Table 1. Figure 1 As shown in the figure, the relationship between hydrogen content and hydrogen pressure is shown in the figure Figure 2 shown.
[0057] Example 4
[0058] This embodiment provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La 0.2 Y 0.05 Nd 0.05 Ca 0.3 Mg 0.4 Ni 3.3 Co 0.10 Fe 0.10 Zn 0.10 .
[0059] The preparation method of the non-stoichiometric hydrogen storage alloy comprises the following steps:
[0060] (1) According to the general composition formula, 30 g of metal raw materials were placed in a quartz crucible, with Mg placed at the bottom, Ca, Co, Fe, Zn, La placed on the top, and Nd and Y sprinkled on the surface. The crucible was first evacuated to 2.0 × 10 -3 Pa and then introduce argon gas to -0.02MPa, and then carry out induction melting, the melting time is 3min, the temperature during melting is controlled by the power of the melting furnace, the power of the first 40s is 5kw, the power is 10kw thereafter, and the power of the last 20s is 15kw, to obtain a cast alloy;
[0061] (2) The cast alloy obtained in step (1) and 100% of the theoretical amount of Mg and 30% of the theoretical amount of Ca were coated with tantalum sheets and placed in a quartz tube, which was first evacuated to 2.0×10 -3Pa and then introduce argon until the vacuum degree is -0.06MPa to seal the tube, anneal the sealed alloy, heat it to 1000℃ at a rate of 20℃ / min, keep it warm for 22h, and then let it cool naturally, mechanically grind the annealed alloy to remove the black oxide scale, then crush the alloy to obtain a bulk alloy, and then put the alloy block into a quartz glass tube with an opening at the lower end, and then place it vertically in the induction melting coil of the belt-spinning machine cavity, evacuate the cavity, and fill the cavity with protective gas through the belt-spinning machine gas tank, adjust the gas pressure of the gas tank to be greater than the cavity pressure, so that the induction melted alloy material falls to the surface of the rotating copper roller and is thrown out, the belt-spinning machine linear speed is controlled to 6m / s, and the alloy sheets after belt spinning are mechanically polished to remove the black oxide scale, mechanically crushed and sieved through 100 mesh to obtain a non-stoichiometric hydrogen storage alloy.
[0062] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this example are listed in Table 1.
[0063] Example 5
[0064] This embodiment provides a non-stoichiometric hydrogen storage alloy, and the composition of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0065] Compared with Example 1, the method for preparing the non-stoichiometric hydrogen storage alloy is the same as Example 1 in that the power of the smelting furnace is maintained at 18W during the induction smelting process in step (1).
[0066] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this example are listed in Table 1.
[0067] Example 6
[0068] This embodiment provides a non-stoichiometric hydrogen storage alloy, and the composition of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0069] Compared with Example 1, the method for preparing the non-stoichiometric hydrogen storage alloy is the same as Example 1 in that the power of the smelting furnace is maintained at 3 kW during the induction smelting process in step (1).
[0070] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this example are listed in Table 1.
[0071] Example 7
[0072] This embodiment provides a non-stoichiometric hydrogen storage alloy, and the composition of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0073] Compared with Example 1, the method for preparing the non-stoichiometric hydrogen storage alloy has the following characteristics: the annealing temperature in step (2) is 850° C., and the rest is the same as Example 1.
[0074] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this example are listed in Table 1.
[0075] Example 8
[0076] This embodiment provides a non-stoichiometric hydrogen storage alloy, and the composition of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0077] Compared with Example 1, the method for preparing the non-stoichiometric hydrogen storage alloy has the following characteristics: the annealing temperature in step (2) is 1050° C., and the rest is the same as Example 1.
[0078] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this example are listed in Table 1.
[0079] Comparative Example 1
[0080] This comparative example provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La 0.4 Ce 0.05 Y 0.05 Er 0.05 Mg 0.55 Ni 3.4 Co 0.10 Al 0.10 .
[0081] The preparation method of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0082] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this comparative example are listed in Table 1. The relationship curve between the hydrogen absorption amount and time is shown in Table 1. Figure 1 As shown in the figure, the relationship between hydrogen content and hydrogen pressure is shown in the figure Figure 2 shown.
[0083] Comparative Example 2
[0084] This comparative example provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La 0.1 Ce 0.05 Y 0.05 Ca 0.5 Mg 0.3 Ni 3.5 Co 0.05 Al 0.05 .
[0085] The preparation method of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0086] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this comparative example are listed in Table 1. The relationship curve between the hydrogen absorption amount and time is shown in Table 1. Figure 1 shown.
[0087] Comparative Example 3
[0088] This comparative example provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La2Ce 0.05 Y 0.05 Ca 0.3 Mg 0.3 Ni 3.5 Co 0.05 Al 0.05 .
[0089] The preparation method of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0090] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this comparative example are listed in Table 1. The relationship curve between the hydrogen absorption amount and time is shown in Table 1. Figure 1 shown.
[0091] Comparative Example 4
[0092] This comparative example provides a non-stoichiometric hydrogen storage alloy, wherein the composition of the non-stoichiometric hydrogen storage alloy is La 0.3 Ce 0.05 Y 0.5 Ca 0.3 Mg 0.3 Ni 3.5 Co 0.05 Al 0.05 .
[0093] The preparation method of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0094] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this comparative example are listed in Table 1.
[0095] Comparative Example 5
[0096] This comparative example provides a non-stoichiometric hydrogen storage alloy, and the composition of the non-stoichiometric hydrogen storage alloy is the same as that of Example 1.
[0097] Compared with Example 1, the method for preparing the non-stoichiometric hydrogen storage alloy does not include step (2), and the rest is the same as Example 1.
[0098] The hydrogen storage performance results of the non-stoichiometric hydrogen storage alloy prepared in this comparative example are listed in Table 1.
[0099] Comparative Example 6
[0100] This comparative example provides a hydrogen storage alloy, the composition of the hydrogen storage alloy is La 0.4 Ce 0.05 Y 0.05 Er 0.05 Mg 0.5 5Ni 2.8 Co 0.10 Al 0.10 .
[0101] The preparation method of the hydrogen storage alloy is the same as that of Example 1.
[0102] The hydrogen storage performance results of the hydrogen storage alloy prepared in this comparative example are listed in Table 1.
[0103] Table 1
[0104] Maximum hydrogen absorption capacity (wt%) Effective hydrogen release amount (wt%) Hydrogen release platform pressure (MPa) Example 1 2.05 1.90 0.24 Example 2 2.00 1.73 0.43 Example 3 1.81 1.59 0.37 Example 4 1.95 1.55 0.31 Example 5 1.98 1.60 0.23 Example 6 1.94 1.56 0.27 Example 7 1.97 1.65 0.15 Example 8 1.96 1.70 0.25 Comparative Example 1 1.75 0.30 0.01 Comparative Example 2 1.14 0.61 0.15 Comparative Example 3 1.25 0.35 No platform Comparative Example 4 1.22 1.11 1.05 Comparative Example 5 2.01 0.70 No platform Comparative Example 6 1.77 1.15 0.15
[0105] It can be seen from Table 1 that:
[0106] (1) The maximum hydrogen absorption capacity, effective hydrogen release capacity and hydrogen release platform pressure of the non-stoichiometric hydrogen storage alloys prepared in Examples 1-4 of the present invention are all at a relatively high level, such as Figure 1 and 2 As shown, the maximum hydrogen storage capacity is higher than 1.8wt%, the effective hydrogen release capacity is higher than 1.55wt%, the platform pressure is higher than the atmospheric pressure, and it is easy to activate, the hysteresis of hydrogen absorption and desorption is small, and the alloy shows good hydrogen storage performance.
[0107] (2) Compared with Example 1, in Examples 5 and 6, when the power used in the smelting process is too high or too low, the maximum hydrogen absorption and effective hydrogen release of the hydrogen storage alloy are significantly reduced, and it can be seen that the hydrogen storage performance is reduced; in Examples 7 and 8, when the annealing temperature is too high or too low, it may affect the uniformity of the alloy composition, resulting in a decrease in its hydrogen storage performance. It can be seen that the hydrogen storage alloy prepared by the preferred process parameters of the present invention can maximize its hydrogen storage performance.
[0108] (3) Compared with Example 1, Figure 1 and 2As shown, in Comparative Example 1, the alloy does not contain Ca and cannot play a modifying role on the alloy, and the effective hydrogen release amount is significantly reduced. The addition of Ca improves the hydrogen release platform and can increase the hydrogen storage capacity; in Comparative Example 2, excessive Ca content will lead to too little La, the matrix element of the hydrogen storage alloy, thereby reducing the hydrogen storage performance. It can be seen that moderate Ca content plays an important role in the performance of the hydrogen storage alloy; in Comparative Example 3, too high La content will also lead to reduced hydrogen storage performance. An appropriate La ratio can improve hydrogen storage kinetics, reduce hydrogen absorption time, and improve crystal structure, thereby increasing hydrogen storage capacity; in Comparative Example 4, when the Y content is too high, the platform pressure is greatly improved, but the hydrogen storage capacity is still small; in Comparative Example 5, the alloy has no hydrogen release platform pressure, and heat treatment can improve the uniformity of the alloy. Without heat treatment, the platform is destroyed; in Comparative Example 6, relative to the AB3 type hydrogen storage alloy, the non-stoichiometric hydrogen storage alloy provided by the present invention has an improved alloy structure due to the increase in the ratio of the elements B / A on both sides, thereby increasing the platform pressure and hydrogen storage capacity.
[0109] In summary, the non-stoichiometric hydrogen storage alloy provided by the present invention has high hydrogen storage capacity, is easy to activate, has a high platform pressure, and has a small hysteresis in hydrogen absorption and desorption. The preparation method thereof is simple and the cost is low.
[0110] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A non-stoichiometric hydrogen storage alloy, characterized in that: The composition formula of the non-stoichiometric hydrogen storage alloy is La 1-a-b-c RE a Ca b Mg c Ni 3.6-d R d , where 0.05≤a≤0.15, 0.2≤b≤0.4, 0.2≤c≤0.4, 0.1≤d≤0.3; Wherein, RE includes any one or a combination of at least two of Ce, Y, Sm, Nd or Er; R includes any one of Co, Al, Si, Mn, Fe or Zn, or a combination of at least two of them.
2. A method for preparing a non-stoichiometric hydrogen storage alloy as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) vacuum induction melting the metal raw materials according to the general composition formula of the non-stoichiometric hydrogen storage alloy to obtain a cast alloy; (2) The cast alloy obtained in step (1) is sealed, heat treated and stripped in sequence to obtain a non-stoichiometric hydrogen storage alloy.
3. The preparation method according to claim 2, characterized in that: The power of the vacuum induction melting in step (1) is 5-15kw.
4. The preparation method according to claim 2 or 3, characterized in that: The vacuum induction melting time in step (1) is 2-4 minutes.
5. The preparation method according to any one of claims 2 to 4, characterized in that: After the sealing in step (2), the vacuum degree in the sealed container is -0.06 to -0.09 MPa.
6. The preparation method according to any one of claims 2 to 5, characterized in that: The heating rate of the heat treatment in step (2) is 5-20°C / min.
7. The preparation method according to any one of claims 2 to 6, characterized in that: The temperature of the heat treatment in step (2) is 900-1000°C.
8. The preparation method according to any one of claims 2 to 7, characterized in that: The heat treatment time in step (2) is 22-26 hours.
9. The preparation method according to any one of claims 2 to 8, characterized in that: The rotational linear speed of the belt in step (2) is 4-6 m / s.
10. The preparation method according to any one of claims 2 to 9, characterized in that: The preparation method comprises the following steps: (1) subjecting the metal raw materials to vacuum induction melting for 2-4 minutes according to the general composition formula of the non-stoichiometric hydrogen storage alloy, wherein the temperature of the vacuum induction melting is controlled by the power of the melting furnace, which is 5-15 kW, to obtain a cast alloy; (2) The cast alloy obtained in step (1) and 60-100% of the theoretical amount of Mg and 20-30% of the theoretical amount of Ca are coated with tantalum sheets and placed in a container. The container is evacuated and then filled with inert gas to a vacuum degree of -0.06 to -0.09 MPa for sealing. The temperature is then raised to 900-1000°C at a rate of 5-20°C / min for heat treatment for 22-26 hours. After cooling, a belt spinning machine is used for belt spinning treatment. The rotation linear speed during belt spinning is 4-6 m / s to obtain a non-stoichiometric hydrogen storage alloy.
Citation Information
Patent Citations
Non-stoichiometric LaNi5-based cobalt-free hydrogen storage alloy and its preparation method
CN102286678A
AB5 type rare earth hydrogen storage alloy for tritium storage and preparation method of AB5 type rare earth hydrogen storage alloy
CN104561661A
Heat treatment method and application of hydrogen storage alloy containing low-melting-point volatile metals
CN109136799A
La-Mg-Ni-series hydrogen storage material and preparation method thereof
CN111636012A
Annealing method of La-Mg-Ni series hydrogen storage alloy
CN115354250A